Assessment of Phubbing, Smart Phone Addiction and Related Psychological Variables among Dental Undergraduates: A Multicentric Study - Deeksha Gijwani; Manu Batra; Aanchal Jindal; Dwivedi R. Vishnupratap; Puneet Kaur (Wolters Kluwer Medknow Publications, 2024)
Background: Internet Addiction and phubbing are prevalent disruptive behaviours among students. The aim of this study was to assess the relationship between phubbing, smartphone addiction and some of the related psychological effects among dental undergraduates. Materials and Methods: A multi-centric cross-sectional pre-validated questionnaire-based study was conducted among undergraduate students of five different dental colleges across India. The questionnaire included the Phubbing Scale, Barratt Impulsiveness Scale (BIS), Smartphone Application-based Addiction Scale (SABAS), and Rosenberg Self-Esteem Scale (RSES). The data were analysed with IBM SPSS version 21, followed by a t-test, analysis of variance (ANOVA), and Spearmen's co-relation to find the association between different psychological variables among study subjects. Results: The total sample comprise of 1226 with mean age of 22.35. The SABAS showed a higher mean ± standard deviation (SD) score (3.17 ± 0.93). The Phubbing Scale showed a positive correlation with the SABAS (0.658), the results were found to be highly statistically significant (P = 0.01). Conclusion: The present study found a higher prevalence of phubbing and smartphone addiction among dental students. Our results showed that impulsiveness leads to internet addiction and thus phubbing is becoming a way to find solace during communication to escape anxiety and distress.